2008
DOI: 10.1111/j.1756-185x.2008.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of juvenile idiopathic arthritis in Bangladesh: experience from a tertiary hospital

Abstract: Objective:  To present our experience of juvenile idiopathic arthritis (JIA) patients in terms of clinical presentation and to observe if there is any difference in clinical presentation of our children from that in the Western world. Methodology:  A cross‐sectional observational study was carried out in the paediatric rheumatology follow‐up clinic run by the Department of Child Health, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, during the study period of January 2004 to April 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
4
13
1
Order By: Relevance
“…Previous studies from our country also reported long duration and very high disability and severity of JIA patients at presentation. 21,22 Moderate response was found as 93.3% at 12 weeks and 92.3% at 24 weeks among cases and 71.5% and 85.7% among controls at 12 weeks and 24 weeks respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies from our country also reported long duration and very high disability and severity of JIA patients at presentation. 21,22 Moderate response was found as 93.3% at 12 weeks and 92.3% at 24 weeks among cases and 71.5% and 85.7% among controls at 12 weeks and 24 weeks respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The data from Europe and North America suggested that girls outnumber boys in JIA . Very few data are available from tertiary level hospitals in Bangladesh, where it was found that 47% of JIA patients had polyarticular and 34.1% had oligoarticular arthritis, and the girl : boy ratio was 1 : 2 . These study findings were different from those of Western countries.…”
Section: Introductionmentioning
confidence: 61%
“…However; few reports are available on JIA from developing countries. Very scanty reports on JIA are available in Bangladesh from a tertiary level hospital regarding clinical aspects of the disease …”
Section: Discussionmentioning
confidence: 99%
“…There is an association of low BMD with duration of disease (3). In Bangladesh it is reported that majority of JIA cases are diagnosed after a long duration (4).…”
Section: Bangabandhu Sheikh Mujib Medical University Bangladeshmentioning
confidence: 99%
“…These features, rather than joint count, represent a more pertinent category, comprising ANA positive oligoarthritis, ANA positive RF negative polyarthritis and ANA positive psoriatic arthritis [2]. Second, the use of anti-CCP allowed the identification of a subgroup of polyarthritis associated with erosive disease and poor radiographic outcome [4]. Third, the use of advanced imaging like ultrasound and MRI showed superiority to clinical examination in the number of affected joints, making a classification based on the joint count somehow inadequate [5].…”
mentioning
confidence: 99%